Feeling the slope?: Teleoperation of a mobile robot using a 7DOF haptic device with attitude feedback - Luz, R.; Pereira, A.; Corujeira, J.; Krueger, T.; Beck, J.; Den Exter, E.; Chupin, T.; Silva, J. L.; Ventura, R. (2023 32nd IEEE International Conference on Robot and Human Interactive Communication (RO-MAN), 2023)
A well-known challenge in rover teleoperation is the operator’s lack of situational awareness (SA). This often leads to an inaccurate perception of the rover’s status and surroundings and, consequently, to faulty decision-making by the operator. We present a novel teleoperation interface to control the locomotion of a ground rover with a 7DOF force feedback device (sigma.7), while providing haptic feedback to ensure appropriate SA. In particular, the device provides proprioceptive cues to convey the rover’s attitude. This can be particularly useful for environments with insufficient visual cues to estimate attitude (e.g., a cave). In systematic experimental trials controlling a robot in an outdoor environment, we evaluated the validity of employing sigma.7 as an alternative to a standard joystick. We tested the use of attitude as an aid to situational awareness. We found no significant detriment in manoeuvrability compared to a conventional joystick, thus validating the sigma.7 as an effective control device. Regarding SA, results showed no statistical difference between the visual and haptic cues for attitude feedback, thus validating the haptic method as an effective alternative to offloading the visual channel by conveying attitude information through the haptic channel instead of visual cues. Finally, qualitative observations of the participant’s behaviour during the experiments showed that operators with haptic feedback were comprehensively aware of the rover’s status.